Study of the conditions of fracture at explosive compaction of powders - Andrey E. Buzyurkin; Evgeny I. Kraus; Yaroslav L. Lukyanov (Fracture and Structural Integrity)
Joint theoretical and experimental investigations have allowed to realize an approach with use of mathematical and physical modeling of processes of a shock wave loading of powder materials.In order to gain a better insight into the effect of loading conditions and, in particular, to study the effect of detonation velocity, explosive thickness, and explosion pressure on the properties of the final sample, we numerically solved the problem about powder compaction in the axisymmetric case.The performed analysis shows that an increase in the decay time of the pressure applied to the sample due to an increase of the explosive thickness or the external loading causes no shrinkage of the destructed region at a fixed propagation velocity of the detonation wave. Simultaneously, a decrease in the propagation velocity of the detonation wave results in an appreciable shrinkage of this region.